Introductory management science decision modeling with spreadsheets - Eppen, Gary D. 1936-; Gould, F.J. (Floyd Jerome) 1936- (Prentice Hall, 1998)
This highly-esteemed text introduces readers to the key ideas of modeling and management decision making that will be important to them throughout their careers. Addressing the needs of readers interested in both business administration and decision science careers, the book provides a conceptual foundation for all topics and the role of spreadsheet modeling techniques in the larger context of business decision-making.